Ecological factors associated with areas of high tuberculosis diagnosis delay. (July 2022) - Soares, P.; Aguiar, A.; Leite, A.; Duarte, R.; Nunes, C.
Abstract: Objective: We aimed to identify areas of high tuberculosis (TB) diagnosis delay in mainland Portugal in 2017 and ecological factors associated with these areas. Study design: This was an ecological study. Methods: We considered all notified pulmonary TB cases from the Portuguese National Tuberculosis Surveillance System in mainland Portugal. Diagnostic delays were calculated at the municipality level. Demographic variables, proxies for TB awareness, health services capacity indicators, and socio-economic variables were included and extracted from official databases, such as Statistics Portugal, Ministeries, Foreigners and Border Services. We used spatial analysis to identify areas of high delay in 2017 and logistic generalised additive models to identify ecological factors associated with the identified cluster. Results: We identified an area of high delay in 2017 in the South region of the country. Overall, municipalities with a smaller population density, smaller proportion of unemployed, fewer health centres and higher old-age dependency ratio, proportion of men, TB incidence, proportion of immigrants and high school dropout had a higher probability of belonging in a high delay area. Conclusion: The role of primary health care in TB diagnosis should be further explored. Interventions should address factors interplaying at the local and individual levels. Policies influencing social and health conditions, leading to changes in individual behaviour, can lead to sustained improvements over time.